Majmuʿah bih khaṭṭ-i Mullā Ṣadrā : Yād dāshthā-yi Qurʾānī va tafsīr-i āya-yi nūr az Mullā Ṣadrā, Muntakhab-i Baḥr al-Ḥaqāʾiq Najm al-Dīn-i Dāyah va al-Taʾwīlāt-i ʿAbd al-Razzāq-i Kāshī - Shīrāzī, Ṣadr al-Dīn, (Miras Maktoob, ISBN: 9789004365452., 2019)
The Islamic manuscript has many forms and shapes, from notes on a scrap of paper to the most preciously illuminated manuscript that can compete with the best one can find in the western world. Usually, a text would be written out at least twice: first as a draft and then as a clean copy from which later copies would be made. Usually, draft versions would either be destroyed, or washed and dried as a means to save paper, or used as reinforcement material by the bookbinder. Thus very few drafts have come down to us. And this is precisely what lends the present manuscript, containing a draft commentary on Qurʾān 24:35 (the celebrated Light Verse) by the famous 11th/17th-century philosopher Ṣadr al-Dīn Shīrāzī (d. 1050/1640) its special interest. Also in this manuscript: sundry notes on the Qurʾān and excerpts from two works by Najm al-Dīn Dāya (d. 654/1256) and ʿAbd al-Razzāq Kāshī (d. 736/1336)